2017
DOI: 10.3329/nimcj.v8i2.32553
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile of Kawasaki Disease (KD) in Children admitted at Dhaka Shishu Hospital

Abstract: Background : Kawasaki disease (KD) is an acute, febrile, self-limiting vasculitis of the medium-and small-sized arteries of unknown etiology. Recently its incidence is increasing worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…19 According to some of the previous studies, this accounts for about 15-20% of all cases occurring less than 1 year of age. [12][13][14][15][16][17][18][19] In our study, we found all patients below 6 months of age presented as IKD, which is 30% of all IKD patients. As per sex is concerned, we found some male preponderance at male female ration of 1.38: 1, which corresponds with other studies.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…19 According to some of the previous studies, this accounts for about 15-20% of all cases occurring less than 1 year of age. [12][13][14][15][16][17][18][19] In our study, we found all patients below 6 months of age presented as IKD, which is 30% of all IKD patients. As per sex is concerned, we found some male preponderance at male female ration of 1.38: 1, which corresponds with other studies.…”
Section: Discussionmentioning
confidence: 87%
“…7 In Bangladesh, the incidence of KD is still unknown. 14 Kawasaki disease can present in two ways. Our study shows that 68% and 32% of children presented as typical and incomplete KD respectively, which is consistent with other study findings.…”
Section: Discussionmentioning
confidence: 99%